Classical Hodgkin Lymphoma in pathological anatomy department at Edgardo Rebagliati Martins National Hospital during 2015 to 2019: Linfoma Hodgkin Clásico en el departamento de anatomía patológica del Hospital Nacional Edgardo Rebagliati Martins durante los años 2015 a 2019. - Quiñones Ávila, María del Pilar (2021)
Introduction: Hodgkin lymphomas are B-cell lymphoid neoplasms histologically characterized by a mixed inflammatory cellular component and few Hodgkin/Reed-Sternberg neoplastic cells. Classical Hodgkin Lymphoma (CHL) represents 10% of all lymphoma cases and 85% of all Hodgkin Lymphomas. According to the current World Health Organization classification, CHL is divided into 4 types: Nodular Sclerosing (NS), Mixed Cellularity (MC), Lymphocyte-Rich (LR), and Lymphocyte-Depleted (LD). Objetive: We reviewed all cases of Classical Hodgkin Lymphoma in the Pathological Anatomy Department at Edgardo Rebagliati Martins National Hospital during 2015 to 2019, in order to determine the most frequent type, the incidence according to age and gender, phenotypical characteristics and relation to Epstein Barr Virus (EBV). Materials and Methods:  We performed a retrospective descriptive case study of Classical Hodgkin Lymphoma and its 4 clinical-pathological types in the Pathological Anatomy Department at Edgardo Rebagliati Martins National Hospital during 2015 to 2019. 72 patients were identified with Classical Hodgkin Lymphoma diagnosis, of which only 64 were selected for the study. The exclusion criteria were the absence of confirmatory immunohistochemical tests and relapse cases. Results: The most frequent type observed was Nodular Sclerosing with 34 cases (53.12%) and the least frequent type was Lymphocyte-Rich with 2 cases (3.12%). Likewise, a predominance in the male gender was observed, with 42 cases, 20 of which were Nodular Sclerosing and 14 not classified, as the most frequent types, and a greater incidence among those 41 to 50 years of age, without detection of the bimodal peak referenced in international literature. The most frequent immunohistochemical profile of Hodgkin/ Reed- Sternberg was CD15 and CD30 positive, with CD45 negative. EBV was present in 36% of cases and is more frequent in the Mixed Cellularity and Lymphocyte-Depleted types. Conclusions: Classical Hodgkin Lymphoma is a group of lymphoid neoplasms with clinical, histological, and phenotypically defined characteristics. It is more frequent in men between 41 and 50 years of age. A complete clinical information and a good biopsy, preferably excisional, is required for an adequate diagnosis. The Nodular Sclerosing type is the most frequent and the Lymphocyte-Rich is the least frequent type. Hodgkin/ Reed- Sternberg cells are usually CD-15 and CD-30 positive and CD-45 negative. The Pax-5 mild positivity allows it to be differentiated from B-cell Non-Hodgkin Lymphomas. EBV is most frequent in Mixed Cellularity and Lymphocyte-Depleted types.